2019
DOI: 10.1051/0004-6361/201936202
|View full text |Cite
|
Sign up to set email alerts
|

Photophoresis in the circumjovian disk and its impact on the orbital configuration of the Galilean satellites

Abstract: Jupiter has four large regular satellites called the Galilean satellites: Io, Europa, Ganymede, and Callisto. The inner three of the Galilean satellites orbit in a 4:2:1 mean motion resonance; therefore their orbital configuration may originate from the stopping of the migration of Io near the bump in the surface density distribution and following resonant trapping of Europa and Ganymede. The formation mechanism of the bump near the orbit of the innermost satellite, Io, is not yet understood, however. Here, we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
(104 reference statements)
0
3
0
Order By: Relevance
“…Moreover, a recent work by Arakawa & Shibaike (2019) found that photophoresis in the CJD stops the inward drift of dust particles near the orbit of Io and carves an inner cavity in a broad range of initial conditions. This result also supports our assumption of the inner cavity strongly.…”
Section: Inner Cavitymentioning
confidence: 99%
“…Moreover, a recent work by Arakawa & Shibaike (2019) found that photophoresis in the CJD stops the inward drift of dust particles near the orbit of Io and carves an inner cavity in a broad range of initial conditions. This result also supports our assumption of the inner cavity strongly.…”
Section: Inner Cavitymentioning
confidence: 99%
“…For large moons, such as Io, Europa, Ganymede, and Callisto around Jupiter, and Titan orbiting Saturn, however, it is favorable to have a gaseous circumplanetary disk (CPD) for their formation. Models for CPDs were proposed and the formation of Galilean moons in the disks has been discussed (Canup & Ward 2002Mosqueira & Estrada 2003a,b;Estrada & Mosqueira 2006;Sasaki et al 2010;Ogihara & Ida 2012;Miguel & Ida 2016;Fujii et al 2017;Cilibrasi et al 2018;Shibaike et al 2019;Arakawa & Shibaike 2019). Saving satellites from inward migration and configuring a system in a Laplace resonance are current topics of strong interest.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, photophoresis has been put on firm ground in recent years by experiments, and analytical models have been derived based on these experiments. In any case, whenever particle motion in a gaseous disk is considered with any kind of directed radiation being present, photophoresis influences particle motion strongly Wurm & Krauss 2006a;Teiser & Dodson-Robinson 2013;Loesche et al 2016a;Cuello et al 2016;Arakawa & Shibaike 2019). Collective motion.…”
Section: Particle Transportmentioning
confidence: 99%